2006
DOI: 10.1021/la060184g
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic and Voltammetric Characterization of Bioanalytical Platforms Based on Lactate Oxidase

Abstract: A microscopic and voltammetric characterization of lactate oxidase- (LOx-) based bioanalytical platforms for biosensor applications is presented. In this context, emphasis is placed on amperometric biosensors based on LOx that have been immobilized by direct absorption on carbon surfaces, in particular, glassy carbon (GC) and highly ordered pyrolytic graphite (HOPG). The immobilized LOx layers have been characterized using atomic force microscopy (AFM) under liquid conditions and cyclic voltammetry. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 28 publications
0
22
0
3
Order By: Relevance
“…[20][21][22][23][24][25][26][27][28][29] But, an important problem in GC application is the electrochemical-response reproducibility related to the electrode pretreatment. 30,31 Diverse investigations showed that the electrodes obtained by different voltammetric methods had different behaviors to the adsorption of organic molecules.…”
mentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27][28][29] But, an important problem in GC application is the electrochemical-response reproducibility related to the electrode pretreatment. 30,31 Diverse investigations showed that the electrodes obtained by different voltammetric methods had different behaviors to the adsorption of organic molecules.…”
mentioning
confidence: 99%
“…Tapping mode has been developed in an aqueous environment, thus allowing characterization of the enzyme electrodes in their working state. Indeed “the biological relevance of dry samples might be questioned” since “imaging under ambient conditions implies the application of higher forces on the protein, which could damage or distort the imaged structures” . However AFM can rarely provide information about the catalytic activity of immobilized enzymes, although we present here an example where time resolved AFM has enabled to visualize motions of protein domains during the catalytic cycle (see part 8).…”
Section: Microscopy and Nanoscopymentioning
confidence: 99%
“…First of all, the LOx were immobilized by direct absorption on glassy carbon electrodes and highly ordered pyrolytic graphite and the LOx layers has been characterized using microscopic techniques. The lactate could be amperometrically determined [200]. In a new report, it was presented a lactate biosensor based on the immobilization of lactate oxidase (LOx) using two different strategies including direct adsorption and covalent binding onto gold surfaces.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%